Isolation, culture and characterization of Arsenophonus symbionts from two insect species reveal loss of infectious transmission and extended host range - Nadal-Jimenez, Pol; Parratt, Steven R.; Siozios, Stefanos; Hurst, Gregory D. D. (Frontiers in Microbiology, 2023)
Vertically transmitted ‘Heritable’ microbial symbionts represent an important component of the biology and ecology of invertebrates. These symbioses evolved originally from ones where infection/acquisition processes occurred within the environment (horizontal transmission). However, the pattern of evolution that follows transition from horizontal to vertical transmission is commonly obscured by the distant relationship between microbes with differing transmission modes. In contrast, the genus Arsenophonus provides an opportunity to investigate these processes with clarity, as it includes members that are obligate vertically transmitted symbionts, facultative vertically transmitted symbionts, strains with mixed modes of transmission and ones that are purely horizontally transmitted. Significantly, some of the strains are culturable and amenable to genetic analysis. We first report the isolation of Arsenophonus nasoniae strain aPv into culture from the ectoparasitic wasp Pachycrepoideus vindemmiae and characterize the symbiosis. We demonstrate maternal vertical transmission and find no evidence for paternal inheritance, horizontal transmission or reproductive parasitism phenotypes. This leads us to conclude this strain, in contrast to related strains, is a facultative heritable symbiont which is likely to be beneficial. We then report the serendipitous discovery and onward culture of a strain of Arsenophonus (strain aPb) from the blue butterfly, Polyommatus bellargus. This association extends the range of host species carrying Arsenophonus nasoniae/ Arsenophonus apicola symbionts beyond the Hymenoptera for the first time. We perform basic metabolic analysis of the isolated strains using Biolog plates. This analysis indicates all strains utilize a restricted range of carbon sources, but these restrictions are particularly pronounced in the A. nasoniae aPv strain that is solely vertically transmitted. Finally, we demonstrate the Arsenophonus sp. strain aPb from the blue butterfly can infect Galleria waxworms, providing a model system for investigating the functional genetics of Arsenophonus-insect interactions.